INTELLECTUAL PROPERTY RIGHTS AS OBJECT OF FINANCING GUARANTEE IN PERSPECTIVE SHARIA ECONOMIC LAW - Diding Jalaludin; Piqi Rizqi Padhilah; Umar Rojikin; Muhamad Kholid; Tatang Astarudin (JURNAL HAKAM, 2025)
This article examines the status of Intellectual Property (IP) as collateral for financing within the framework of Islamic Economic Law. IP—covering trademarks, patents, copyrights, industrial designs, trade secrets, and communal intellectual property—embodies reputation and economic value, thereby raising the question of whether it may qualify as māl (property) and function as marhūn (pledged collateral). Employing a descriptive-analytical method and a juridical-empirical approach through library research, the study analyzes statutory regulations on IP-based security, relevant fatwas, and contemporary Islamic legal scholarship. The findings suggest that IP conceptually corresponds to ḥaqq al-ibtikār (creative/authorial right), which is increasingly recognized as a proprietary right containing both economic and moral dimensions. Its legitimacy is frequently grounded in ‘urf (recognized custom) and maṣlaḥah mursalah (public interest), supporting the permissibility of utilizing IP as collateral under the general maxim that commercial transactions are allowed unless proven otherwise. The article further proposes Sharia-compliant operational models—such as rahn combined with murābaḥah, ijārah, istiṣnā‘, and profit-sharing schemes (muḍārabah/mushārakah)—subject to strict avoidance of ribā, gharar, and maysir, and contingent upon reliable valuation standards, secondary-market readiness, and enforceable execution mechanisms. Divergent scholarly views are mapped, particularly regarding intangibility, valuation volatility, and moral-right constraints.